The allocation of public expenditure and economic growth. - Agénor, Pierre-Richard; Neanidis, Kyriakos C. (Manchester School (14636786), 2011)
This paper studies the optimal allocation of government spending between health, education and infrastructure in an endogenous growth framework. Infrastructure affects not only the production of goods but also the supply of health and education services. The production of health (education) services depends also on the stock of human capital (health services). Transitional dynamics associated with budget-neutral shifts in the composition of expenditure are analyzed, and growth- and welfare-maximizing allocation rules are derived and compared. The discussion highlights the role played by the externalities associated with all three types of public services in the health and human capital technologies. Reprinted by permission of the publisher.